The Cochrane Ear, Nose and Throat Disorders Group. - Bellorini, J; Dorée, C; Chamberlain, I; Burton, M (2007)
The Cochrane Ear, Nose and Throat Disorders Group is part of The Cochrane Collaboration and produces high-quality systematic reviews of interventions in otolaryngology and a register of all published and unpublished randomized and controlled trials in otolaryngology-head and neck surgery. The editorial base in Oxford provides support for volunteer reviewers who are practitioners, epidemiologists, or patients wishing to undertake reviews, and these are published in The Cochrane Library (www.thecochranelibrary.com). Participation and group membership is free and open to all. We describe here how the group is organized, how it undertakes its core activities, and how you, the reader, can become involved.